Anthropometric profile of FIVB volleyball girls' U18 World Championship volleyball players according to the playing position - World Championship 2017 - Jahandideh, A.; Rohani, H.; Hemmat, S. (International Journal of Sport, Exercise and Health Research, 2021)
Identifying the anthropometric characters of adolescent elite players may be useful in developing the recognition of volleyball talents and key physical abilities needed to perform at a high level. The purpose of this study was to describe anthropometric characteristics, including height, weight, body mass index (BMI), spike height, and block height in elite volleyball youth players participating in the 2017 FIVB Volleyball Girls' U18 World Championship. Also, comparisons of these parameters were evaluated based on individual game position (libero, setter, middle blocker, outside hitter, opposite), team continent, and team rank. The variables studied in this study were extracted from the list of players registered on the website of the InternationalVolleyball Federation (FIVB) and included 240 players of 20 teams. The results of one-way ANOVA showed that players in the G1 group (rank 1 to 4) had higher height, weight, spike height, and block height than other groups (rank 5 to 20). Also, the middle blockers had the tallest height (185.9 cm), weight (71.4 kg), spike height (294.5 cm) and block height (282.7 cm). This study presents anthropometric data that show different levels of success for elite girls' volleyball players in the 2017 championship. This information should serve as a reference for average body height, weight, BMI, spike height, and block height for identifying athletic talents for various positions in volleyball.